Saponins of Agave: Chemistry and bioactivity - Sidana, J.; Singh, B.; Sharma, O. P.
The genus Agave comprises more than 400 species with geographical presence in the tropical and sub-tropical regions of the world. These plants have a rich history of folkloric use and are known for a wide spectrum of applications. Secondary metabolites of diverse chemical classes have been reported from Agave species. Owing to their pharmacological significance, the steroidal saponins of Agave have caught the attention of phytochemists, biologists and drug discovery scientists. The present review describes 141 steroidal saponins and sapogenins and covers the literature published from 1970 to 2015. It is a comprehensive and coherent presentation of the structures, methods of chemical profiling, structure elucidation and biological activities of the saponins and sapogenins reported from Agave. The article provides a perspective of the research on steroidal compounds of Agave.
Keywords: AGAVE; AGAVACEAE; SAPONINS; SAPOGENINS; SPIROSTANOL GLYCOSIDES; FUROSTANOL GLYCOSIDES